Pengaruh Kepercayaan Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Lion Parcel Di Kota Tebing Tinggi - Bobby Hartanto (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
The development of the need for product delivery services as a necessary facility, even in modern times, many people open online businesses by sending products from one area to a different area. This study aims to determine the effect of Trust and Service Quality on customer satisfaction at Lion Parcel in Tebing Tinggi City. This type of research is quantitative. This study used a sample of 50 respondents. Sampling using incidental sampling technique. The test tools used are validity and reliability tests, classical assumption tests, multiple regression analysis, hypothesis testing via t-test, f-test and the coefficient of determination. The test was carried out using SPSS version 25. The results showed that hypothesis 1 tcount (1.031) < ttable (2.0106), as well as a significance value of 0.308 > 0.05 Trust has no significant effect on customer satisfaction. it can be seen that tcount (6.129) > ttable (2.0106), and a significance value of 0.000 <0.05, it can be concluded that hypothesis 2 is accepted, Service Quality has a significant effect on Customer Satisfaction. it can be seen that the variables of Trust and Customer Satisfaction have a significant effect on Customer Satisfaction. It can be seen that Fcount 20.467 > Ftable 2.72, and a significance value of 0.000 <0.05, it can be concluded that hypothesis 3 is accepted, Trust, Service Quality have a joint effect on Customer Satisfaction.